Applications and Lipschitz results of approximation by smooth Picard and Gauss-Weierstrass type singular integrals - Mezei, Razvan A. (CUBO, A Mathematical Journal, 2011)
We continue our studies in higher order uniform convergence with rates and in Lp convergence with rates. Namely, in this article we establish some Lipschitz type results for the smooth Picard type singular integral operators and for the smooth Gauss-Weierstrass type singular integral operators.